Exploring branding as part of the corporate communication strategy of the Girl Guides Association Of South Africa (GGASA) - Snyman, M.E. (Martha Elizabeth) (University of Pretoria, 2013)
Dissertation (MA (Development Communication))--University of Pretoria, 2005.